Contactless electric–field driven Z-alignment of ceramic nanoparticles in polymer electrolyte to enhance ionic conductivity. (July 2020) - Liu, Jiyan; Fang, Wei; Gao, Shuyu; Chen, Yuwei; Chen, Shaoyun; Hu, Chenlong; Cai, Shaojun; Liu, Zhihong; Liu, Xueqing
Abstract: The contactless electric–field accomplishes particles alignment in solution allowing free solvent evaporation without electrochemical decomposition. Herein the nanoparticle Li1+x Alx Ge2-x (PO4 )3 (LAGP) Z-direction (out-of-plane) alignment was driven by a contactless electric field within a cross-linked solid electrolyte of poly(ethylene oxide)/poly(ethylene glycol) diacrylate/lithium bis(trifluoromethylsulfonyl)imide (PEO/PEGDA/LiTFSI). The alignment and chain formation of nanoparticles was verified by scanning electron microscope combining with energy dispersive X-ray spectrometry. Benefiting from this Z-direction alignment, LAGP/PEO/PEGDA/LiTFSI membrane possesses enhanced ionic conductivity and improved flexibility. With 20 wt% LAGP loading, 2.7 times ionic conductivity was achieved in the Z- direction and 1.6 times elongation at breaking was obtained along the membrane surface after alignment. This contactless electrical field method is a new strategy to prepare polymer composite membrane with anisotropic property from solvent-containing system. Graphical abstract: Unlabelled Image Highlights: Z-direction aligned ceramic nanoparticles were constructed with a contactless electric field. Aligned nanoparticles show a high Z-direction ion conductivity. Air-gap electrode favors the solvent evaporation.